2013
DOI: 10.1093/molbev/mst205
|View full text |Cite
|
Sign up to set email alerts
|

Massive Habitat-Specific Genomic Response in D. melanogaster Populations during Experimental Evolution in Hot and Cold Environments

Abstract: Experimental evolution in combination with whole-genome sequencing (evolve and resequence [E&R]) is a promising approach to define the genotype–phenotype map and to understand adaptation in evolving populations. Many previous studies have identified a large number of putative selected sites (i.e., candidate loci), but it remains unclear to what extent these loci are genuine targets of selection or experimental noise. To address this question, we exposed the same founder population to two different selection re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
196
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 145 publications
(213 citation statements)
references
References 51 publications
14
196
3
Order By: Relevance
“…These results confirm the power of the E&R approach in the identification of targets of selection (32). This methodology has been used to identify changes in allele frequencies following selection in complex traits such as developmental time (7), body size (8), hypoxia tolerance (6), increased life span (33), adaptation to high/low temperatures (9,34), and courtship behavior (10,31). These studies have identified a polygenic basis for the studied traits, hampering the identification of candidate genes and a subsequent functional analysis.…”
Section: Discussionsupporting
confidence: 55%
“…These results confirm the power of the E&R approach in the identification of targets of selection (32). This methodology has been used to identify changes in allele frequencies following selection in complex traits such as developmental time (7), body size (8), hypoxia tolerance (6), increased life span (33), adaptation to high/low temperatures (9,34), and courtship behavior (10,31). These studies have identified a polygenic basis for the studied traits, hampering the identification of candidate genes and a subsequent functional analysis.…”
Section: Discussionsupporting
confidence: 55%
“…results are consistent with those of Tobler et al (2014), who observed a massive amount of outlier SNPs around the centromere of chromosome 2 and on 3R. Interestingly, certain regions of the genome show extensive differences in b N e between the replicates, which might be reflecting different selection histories or differences in demography, such as replicatespecific bottlenecks.…”
Section: Heterogeneous Bsupporting
confidence: 89%
“…Nevertheless, systematic forces that result in locally different values of b N e can be detected with a slidingwindow approach, as illustrated with simulations under selection ( Figure S15). The D. melanogaster data set also illustrates this point; i.e., the hypothesized regions under selection coincide with regions of reduced N e (Orozco-terWengel et al 2012;Tobler et al 2014;Franssen et al 2015). For this to be detected, however, most of the allele frequency change has to occur over the sampled time span.…”
Section: Recommendations For Genome-wide Data Setsmentioning
confidence: 81%
“…was studied using both long-term and realized N e . Variation in N e was reported at large scale such as entire chromosome arm (Orozco-terWengel et al 2012;Tobler et al 2014), as well as between gene fragments (Gossmann et al 2011). The other nine species studied in Gossmann et al (2011) also reported statistically significant variation in N e between gene fragments.…”
Section: Causes For the Heterogeneity In N Ementioning
confidence: 85%
“…They observed different rates of genetic drift, as estimated by loss of heterozygosity, among the chromosomes; these rates ranged from very low levels of genetic drift found in the sexual X chromosome to very high levels presented by chromosome 3. Tobler et al (2014) combined experimental evolution and next-generation sequencing (NGS) to detect candidate SNPs associated with thermal adaptation in D. melanogaster. They estimated a chromosome-specific N e for each chromosome, using a total of 1.45 million SNPs.…”
Section: Different Methods Can Be Used To Detect Heterogeneity In N Ementioning
confidence: 99%